Актуализация музыкальной эстетики в творчестве Ф. Грильпарцера - Даценко, Ю.В. (Культура народов Причерноморья, 2013)
В данной статье исследуется актуализация музыкальной эстетики в творчестве Ф. Грильпарцера. В статье рассматривается поэтизация музыкальных мотивов в творчестве австрийского писателя сквозь призму микро и макрообразов его творческого мегаобраза. Выявлены разные формы реализации музыкальной эстетики Ф. Грильпарцера. Исследована музыкальная семантика поэтического наследия поэта, составляющая малоизученную часть произведений Ф. Грильпарцера. У даній статті досліджується актуалізація музичної естетики у творчості Ф. Грільпарцера. У статті розглядається поетизація музичних мотивів в творчості австрійського письменника крізь призму мікро і макрообразів його творчого мегаобраза. Виявлені різні форми реалізації музичної естетики Ф. Грільпарцера. Досліджена музична семантика поетичної спадщини поета, складова маловивченої частини творів Ф. Грільпарцера. This article explores the actualization of musical aesthetics in F. Grillparzer`s works. After Grillparzer’s death much biographical material circulates about him. Some of the prominent writers include F.Grillparzer are presented in the musical topic. The article is considered writing poems of musical motives in the works of the Austrian writer through the prism of microimages and macroimages his creative megaimage. The article is revealed the different forms of Grillparzer`s musical aesthetics. Semantics and mechanisms of mythpoetic structures were defined in the work of the writer. In the article comes to light the world view basis of creation of Astrian dramatist, poet, writer philosophical-aesthetic looks in relation to nature of music. For the honour of the Wiener Schubertbund many well known artists, scientists and politicians were and are proud of being its honorary members, e.g. Franz Grillparzer, Michael Vogl, Ludwig Van Beethoven, Nikollo Paganini, Ferenz List, Felix Mendelson, Clara Wieck, Anna Foehlich. The Grllparzer`s «Serenadе» was performed by Anna Froehlich on piano, her sister Josefine Froehlich (Pepi) as the soloist, and a group of Anna's pupils forming the female chorus. The musical semantics of poetic heritage of insufficiently known part of the Grillparzer`s works is investigated.